Effects of The First 1000 Days of Life Module For Premarital Women Against Knowledge and Attitudes to Prevent Stunting - Zubaeda, Zubaeda; Suhartono, Suhartono; Runjati, Runjati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The first 1000 days of life period is the most frequent period of stunting as well as the best period to prevent and improve the stunting condition, so it needs optimal preparation before entering this period which can be applied to premarital women. This study aims to analyze the effect of giving first 1000 days of life modules to the knowledge and attitude of stunting prevention in Premarital women. This type of research is quasi-experimental pre test-post test with control group design. The number of samples is 60 premarital women divided into two groups. The Result of Paired T-test knowlede and attitude score obtained p value 0.001), while the result of Independen T-test p value of knowledge = 0.002 and attitude = 0.02. The First 1000 days of life modules has more effect on increasing knowledge and attitude of stunting prevention compare premarital class only.